Broadband Dual-Sense Circular-Polarization Reconfigurable Metasurface Antenna for Wearable Applications - Tu Tuan Le; Yong-Deok Kim; Tae-Yeoul Yun (IEEE Access)
This manuscript introduces a broadband dual-sense circular-polarization (CP) reconfigurable coplanar waveguide (CPW)-fed metasurface (MS) antenna for wearable applications. The proposed antenna employs an integration of two vertical stubs, protruding from the ground plane of a CPW-fed monopole antenna, through two p-i-n (PIN) diodes. The proposed antenna has several unique features, including low specific absorption rate (SAR), wide impedance bandwidth (IBW) and axial ratio bandwidth (ARBW), and a simple reconfigurability using only two PIN diodes. The polarization reconfiguration is achieved using a biasing circuit that selectively switches one diode to the ON state while keeping the other in the OFF state. This configuration produces perturbations in the current distribution along the horizontal and vertical axes, exciting CP radiation. By alternating the state of the PIN diodes, the direction of circular polarization is changed. To enhance the ARBW, radiation directivity, and SAR, an MS structure is placed under the fundamental radiator. Two square ring resonators are also added to further improve the ARBW. The proposed antenna is fabricated and verified by measurement in free space, human body, and fresh pork environments, demonstrating good agreement between simulation and measurement results. The antenna is also evaluated on a human tissue model, confirming that its SAR complies with the US and EU safety standards.